Text structure awareness : another look at reading comprehension strategy in L2 Classes. - Heydari, Maryam; Mustapha, Ghazali (The Journal of International Management Studies, 2009)
Researchers have shown that skilled readers use variety of strategies to comprehend written texts (Stanovich, 2000; Sweet & Snow, 2003). Hence many readers are not aware of reading strategies; there is a need of explicit teaching instruction to develop those strategies. In fact, in most English reading classes there is absence of teaching comprehension strategies to readers, the strategy usually employed is, finding the meaning of the unknown vocabularies or translating the texts in to students’ native language, this approach only enables students to comprehend the passage partially. Reading research has indicated that readers’ awareness of different kinds of text structure has been a useful strategy for better comprehension. All texts have certain styles of writing, which not only distinguishes them from other types of texts but they are also of great help in conveying the authors’ messages and recalling the texts. Teachers play an important role in assisting students in developing reading comprehension strategies including expository text structure awareness (Pearson & Duke, 2002).